2023
DOI: 10.1021/acs.chemmater.3c00842
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective of Engineered Lipids and Liposomes: Chemical Design and Functional Application Based on Therapeutic Safety

Abstract: Liposome-based drugs have emerged as highly successful nanomedicines for clinical applications owing to their excellent biocompatibility, biodegradability, and targeting effects. However, the lipids that play a crucial role in most liposome formulations are often engineered rather than natural phospholipids. From this perspective, we outlined the classification of engineered lipids based on their material chemistry, including charged, polymerconjugated, ligand-conjugated, and choline phosphate lipids. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…Both liposomal Dox and PEGylated liposomal Dox (PLD) demonstrated favorable toxicity profiles, with improved cardiovascular security as well as fewer alopecia, myelosuppression, vomiting, and nausea compared to conventional anthracyclines, thereby providing a better alternative for patients with risk factors for cardiovascular disease, and patients who have previously used anthracyclines . Recently choline phosphate (CP) lipids have been developed and found to have high efficacy for cancer therapy . Wang et al demonstrated Dox encapsulated CP liposomes had higher uptake and accumulated in cells compared to phosphatidyl choline (PC) loaded Dox liposomes .…”
Section: Liposomes As a Therapeutic Carriermentioning
confidence: 99%
See 1 more Smart Citation
“…Both liposomal Dox and PEGylated liposomal Dox (PLD) demonstrated favorable toxicity profiles, with improved cardiovascular security as well as fewer alopecia, myelosuppression, vomiting, and nausea compared to conventional anthracyclines, thereby providing a better alternative for patients with risk factors for cardiovascular disease, and patients who have previously used anthracyclines . Recently choline phosphate (CP) lipids have been developed and found to have high efficacy for cancer therapy . Wang et al demonstrated Dox encapsulated CP liposomes had higher uptake and accumulated in cells compared to phosphatidyl choline (PC) loaded Dox liposomes .…”
Section: Liposomes As a Therapeutic Carriermentioning
confidence: 99%
“… 57 Recently choline phosphate (CP) lipids have been developed and found to have high efficacy for cancer therapy. 58 Wang et al demonstrated Dox encapsulated CP liposomes had higher uptake and accumulated in cells compared to phosphatidyl choline (PC) loaded Dox liposomes. 59 This further showed significantly higher cytotoxicity in cancer cells and also inhibited growth of tumor.…”
Section: Liposomes As a Therapeutic Carriermentioning
confidence: 99%
“…A key factor is the nature of their encapsulating material. Liposomes typically utilize widely available natural phospholipids like phosphatidylcholine [ 155 ], while polymersomes are predominantly created from synthetic amphiphilic block copolymers [ 15 ]. This difference significantly impacts the clinical approval process for polymersomes.…”
Section: Prospects and Challenges Of Polymersomes For Clinical Develo...mentioning
confidence: 99%
“…Liposomal drug composition has been the subject of numerous investigations for various biological purposes. In one of the investigations, glutamic acid is successfully used as a cross-linker to conjugate polyethylene glycol (PEG) to the lipid monomer . Postadministration of PEGylated formulations/drugs results in the production of antibodies which bind to PEG selectively showing reduced treatment efficacy. For example, PEGylated proteins and peptides demonstrate anti-PEG antibody responses by the T-cell pathway.…”
Section: Liposomesmentioning
confidence: 99%